2021
DOI: 10.2516/ogst/2021026
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and modeling studies of density and viscosity behavior of a live fluid due to CO2injection at reservoir condition

Abstract: In this study, highly accurate measurements of density and dynamic viscosities of a recombined live oil and its mixture with additional CO2 were performed. The experiments were carried out under pressure and temperature gradients found in Brazilian Pre-salt reservoirs, that is, in the pressure range from (27.6 to 68.9) MPa and at (333.15 and 353.15) K. The assumption of volume change on mixing is evaluated from the experimental results, and the influence of pressure and temperature on the volume change upon mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Crude oil viscosity is an important parameter for screening suitable CO 2 -EOR reservoirs [50]. However, not all the crude oil viscosity of the reservoir is available in the reservoir data.…”
Section: Calculation Of Oil Viscositymentioning
confidence: 99%
“…Crude oil viscosity is an important parameter for screening suitable CO 2 -EOR reservoirs [50]. However, not all the crude oil viscosity of the reservoir is available in the reservoir data.…”
Section: Calculation Of Oil Viscositymentioning
confidence: 99%
“…Many scientific studies have shown that human activity is the main cause of these global problems [1,2]. Indeed, the massive development of transport, the rapid growth of polluting industries, and excessive energy consumption, have largely contributed to the depletion of natural resources and to environmental degradation through the release of greenhouse gases in particular CO 2 , responsible for global warming and climate change [1,[3][4][5]. So, several alternative energy sources derived straightforwardly or in a roundabout from the sun, the wind, hydropower, bioenergy and biofuels or from geothermal energy of the Earth [6] are created and executed to deliver a scope of energy administrations, including power, warming, cooling, and biofuels.…”
Section: Introductionmentioning
confidence: 99%